1996
DOI: 10.1104/pp.111.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of 59Fe-Labeled Fe2+ Influx in Roots of Pea Using a Chelator Buffer System to Control Free Fe2+ in Solution

Abstract: Fe2+ transport in plants has been difficult to quantify because of the inability to control Fe2+ activity in aerated solutions and non-specific binding of Fe to cell walls. In this study, a Fe(II)-3-(2-pyridyl)-5,6-diphenyl-1,2,4-triazine-4[prime]4″-disulfonic acid buffer system was used to control free Fe2+ in uptake solutions. Additionally, desorption methodologies were developed to adequately remove nonspecifically bound Fe from the root apoplasm. This enabled us to quantify unidirectional Fe2+ influx via r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 16 publications
1
36
0
2
Order By: Relevance
“…Most other iron-efficient plants use strategy I and respond to iron deprivation by inducing the activity of membrane-bound Fe(III) chelate reductases that reduce Fe(III) to the more soluble Fe(II) form. The Fe(II) product is then taken up into the roots by an Fe(II)-specific transport system that is also induced by iron-limiting growth conditions (4). Furthermore, the roots of strategy I plants release more protons when iron-deficient, lowering the rhizosphere pH and thereby increasing the solubility of Fe(III).…”
mentioning
confidence: 99%
“…Most other iron-efficient plants use strategy I and respond to iron deprivation by inducing the activity of membrane-bound Fe(III) chelate reductases that reduce Fe(III) to the more soluble Fe(II) form. The Fe(II) product is then taken up into the roots by an Fe(II)-specific transport system that is also induced by iron-limiting growth conditions (4). Furthermore, the roots of strategy I plants release more protons when iron-deficient, lowering the rhizosphere pH and thereby increasing the solubility of Fe(III).…”
mentioning
confidence: 99%
“…Fe uptake in the dicots and the nongrass monocots is mediated by a plasma membrane-bound ferric reductase that transfers electrons from intracellular NADH (Buckhout et al, 1989) to Fe(III) chelates in the rhizosphere (Chaney et al, 1972). The ferrous ions (Fe 2ϩ ) released from the chelates by this process are subsequently transported into the cytoplasm via a separate transport protein (Kochian, 1991;Fox et al, 1996). When Fe deficient, dicot and nongrass monocots stimulate a number of processes to enhance Fe accumulation from the soil.…”
mentioning
confidence: 99%
“…Finally, root Fe 2ϩ influx is regulated by the Fe status of the plant. Fox et al (1996) found that Fe-deficient pea (Pisum sativum L.) seedlings exhibit significantly higher rates of root Fe 2ϩ influx than Fe-sufficient seedlings. In addition to these responses, which are usually linked specifically to Fe accumulation, tissue concentrations of other mineral elements also appear to be influenced by plant Fe status.…”
mentioning
confidence: 99%
“…The ferric ion is then chelated by the released compounds, as well as by soil bacteriosiderophores (Römheld and Marschner, 1983;Bar-Ness et al,1992). Subsequently, chelated Fe 3+ is reduced by a low iron-inducible enzymatic activity present in the plasma membrane of root epidermal cells (Moog and Brüggermann, 1994) and Fe +2 is then absorbed by a specific transporter (Fox et al, 1996). A different strategy to overcome the problem of low iron availability in the soil evolved in grasses (such as rice).…”
Section: Introductionmentioning
confidence: 99%